Blood Politics: Australian Nurses, HIV and the Battle for Rights on the Wards. (November 2018) - Fela, Geraldine
Abstract : In the 1980s and early 1990s, homophobia and prejudice were ubiquitous in Australian HIV/AIDS hospital wards and clinics. The association of HIV/AIDS with "deviant" subjects, namely gay men and intravenous drug users, meant that both patients and health care workers experienced and witnessed discrimination. These wards and clinics however, also became sites of solidarity and collaboration that extended across diverse lines of identity. While some HIV/AIDS nurses were gay men, many were heterosexual working-class women. In a context of increasing industrial radicalism amongst nurses, nurses and their unions played a crucial role in fighting for the rights of people living with and dying from HIV/AIDS. They fought and won a political battle with doctors and surgeons for a socially progressive approach to testing and infection control. Drawing on both archival research and oral testimony, this article considers this important, though under-examined, chapter in Australian labour history.